Design provisions for FRCM systems bonded to concrete and masonry elements. (15th June 2018) - Ceroni, F.; Salzano, P.
Abstract: Fibre Reinforced Cementitious Matrix (FRCM) materials are becoming an alternative strengthening technique to the well-known Fibre Reinforced Polymer (FRP) materials applied by means of epoxy resin, especially for masonry elements. Experimental tests have shown that the performance of elements strengthened with FRCM systems depends on the bond behaviour at both the reinforcement/substrate and grout/grid interface. Because of the novelty of the FRCM technique and the wide spectrum of FRCM materials (both grouts and grids) present on the market, no design indications are now available for such a strengthening technique, for both concrete and masonry elements. In this paper, a critical analysis of the available literature on bond tests on masonry and concrete elements externally bonded with FRCM materials was done, firstly. Successively, the collected results were examined in terms of failure mode and maximum strain in order to identify the main geometric and mechanical properties of the reinforcement and the substrate influencing the performance of the strengthening technique. Regression analyses were, thus, carried out on the collected experimental results, separately for concrete and masonry elements, in order to asses reliable formulations predicting the maximum strain in function of the axial stiffness of the reinforcement, the mechanical properties of the substrate, and the experimentally observed failure modes. Basing on the average provisions of the maximum strain in the FRCM reinforcement, characteristic values were also assessed according to a 'design by testing' procedure.